Drosophila DNp03 descending neurons serve as a hub within a flight saccade network. - Croke, H.; Jang, H.; Ludlow, B.K.; Leung, A.; Eichler, K.; Stürner, T.; Costa, M.; Cohen, I.; Ausborn, J.; von Reyn, C.R. (Current Biology, 2026)
Animals rely on rapid sensorimotor processing to detect and respond to visual stimuli in their environment, yet how sensorimotor networks are organized to generate appropriate behaviors remains unclear. Here, we identify a bilateral pair of descending neurons (DNs), DNp03, as a hub for collision avoidance in flying flies. DNp03 receives visual information related to looming objects approaching on a collision course and connects directly and indirectly to motor neurons of the wings and neck, enabling the coordinated banked turn and head stabilization maneuvers of a rapid saccade. Although DNp03 can drive saccade-like behavior when optogenetically activated, naturalistic looming-evoked saccade behavior relies on a network of interconnected DNs that can partially compensate for DNp03 in its absence. The connectivity of this hierarchical network suggests DNp03 operates in parallel with two additional DN hubs that directly recruit subservient DNs to reinforce and expand behavioral outputs. We also find competition between the saccade network and descending pathways for landing behavior, where direct inhibitory connections from DNp03 reduce the likelihood a fly decides to land on, rather than turn away from, a looming object. Altogether, we provide a detailed mapping of one key sensorimotor pathway from visual inputs to motor outputs to demonstrate how even rapid, innate sensorimotor transformations rely on complex networks. These findings reveal intricate interconnectivity and hierarchy in descending pathways, a strategy that may represent a general principle of motor control across species.